Language use in writing research articles in science, technology, engineering, agriculture and methematics (STEAM) a genre analysis - Abuel, Arsenia A. (2016)
The study reports on the examination of introduction, method, result and discussion (IMRD) sections of research articles in science, technology, engineering, agriculture and mathematics (STEAM) which are written and prepared by non-native speakers (NNS) of English particularly the Filipino professionals. Specifically, this study identified the rhetorical structures of research articles publsihed in Philippine journals in STEAM. The corpus consisted of fifty (50) RAs drawn from a wide range of refereed journals in five discourse communities. The rhetorical structure of research articles was explored via genre analysis. The corpus of research articles (RAs) was analyzed following Swales' framework (1990 & 2004), Kanoksilapatham (2005), Peacock (2011) and Yang and Allison's (2003) model to segment the IMRD structures into sub-units called 'moves' and 'steps,' respectively, according to their communicative functions. Based on the findings, two-level rhetorical structures (moves and steps) of 18 distinct moves: three moves for the Introduction section, four for the Methods section four for the Results section, and seven for the Discussion section characterized research articles (RAs) published in Philippine journals in STEAM. This study provides a basic yet comprehensive and typical model of rhetorical structure for organizing research articles in science, technology, engineering, agriculture and mathematics (STEAM). In this regard, the notion of conforming to the norms and conventions laid down by the discourse community can be used as a means of marshalling ideas into an appropriately ordered text and can be presented in the classroom to raise learner's consciousness of discipline specific genre writing skills.
Keywords: Language; Rhetorical analysis